2020
DOI: 10.3126/jcmc.v10i3.32001
|View full text |Cite
|
Sign up to set email alerts
|

Stress and anxiety among nurses working in tertiary care hospitals in Nepal during COVID- 19 pandemic

Abstract: Background: Healthcare workers like nurses’ are the primary group who come in contact with patients, an important source of exposure to infected cases in healthcare settings. Co­rona Virus Disease 2019 (COVID-19) pandemic has brought all the health care professionals including nurses to work as a frontline member which may bring threat to mental wellbeing. The nurse’s psychological impact including stress and anxiety remains unknown. Hence, this study aimed to assess the stress and anxiety regarding COVID-19 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…Normal anxiety was assessed in 95.05% of participants, and none of them experienced severe anxiety or panic. Similar to the study of Neupane et al [ 19 ] which found that 88.4% of nurses experienced normal anxiety and another 10.5% reported mild to moderate levels of anxiety. A survey in China revealed that less than half of healthcare personnel, notably female nurses caring for patients, exhibit signs of anxiety [ 2 ].…”
Section: Discussionsupporting
confidence: 88%
“…Normal anxiety was assessed in 95.05% of participants, and none of them experienced severe anxiety or panic. Similar to the study of Neupane et al [ 19 ] which found that 88.4% of nurses experienced normal anxiety and another 10.5% reported mild to moderate levels of anxiety. A survey in China revealed that less than half of healthcare personnel, notably female nurses caring for patients, exhibit signs of anxiety [ 2 ].…”
Section: Discussionsupporting
confidence: 88%
“…During the COVID-19 pandemic in Turkey, the participants expressed perceiving high levels of stress when feeling nervous or stressed, when they felt compelled to succeed, when they experienced an unexpected event, and when they were unable to control important things in their lives. During the COVID-19 pandemic, two thirds of the nurses participating in a study in Austria and more than half of those in Nepal perceived moderate stress levels (Hoedl et al, 2020; Neupane et al, 2020). In a cross-sectional study that aimed to determine the prevalence of perceived stress and risk factors among healthcare providers in Ethiopia, the prevalence of perceived stress was found to be very high among healthcare providers, with the highest stress scores found among nurses (Chekole et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…However, study conducted by Neupane MS et al, had 37.6% of nurses with high level of stress and 54.7% of nurses had moderate level of stress. 7 In similar studies done in Brazil where mild to moderate level of peritraumatic distress was found among 52.9% (N=654). 12 Similar type of studies done on Nepalese community people revealed that Mild to moderate peritraumatic distress was found among 17.82% and Covid-19 Peritraumatic Distress index score was 14.67 (SD± 9.09) which was contrast to present study.…”
Section: Discussionmentioning
confidence: 80%
“…Corona Virus Disease 2019 (Covid-19) pandemic has brought all the health care professionals including nurses to work as a frontline member, which may bring threat to mental wellbeing. 6,7 However, evidence regarding the psychological impact and its associated factors of Covid 19 among nurses is not available in Nepal, in this context, this study aimed to evaluate psychological impact and its associated factors of Covid among nurses working in Bharatpur, Nepal.…”
Section: Introductionmentioning
confidence: 99%